Ang Bagong Lumipas-II :1940-1965 - Constantino, Renato. 4 0 16; 5 ([Quezon City] : University of the Philippines Press at Foundation for Nationalist Studies, 1996)
History of the Philippines.
-- 2. 1940-1965.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; 20; History. -- Philippines -- 20; 2